Opinions of UK rescue shelter and rehoming center workers on the problems facing their industry - Stavisky, Jenny; Brennan, Marnie L.; Downes, Martin J.; Dean, Rachel S. (Taylor & Francis, 2017)
Animal shelters exist worldwide to care for and rehome unwanted or straying pets. Previous studies have examined why owners breed unwanted animals, or relinquish their pets to shelters. However, the views of shelter workers, who receive and care for these animals, have previously been largely unexplored. The aim of this study was to investigate the perceptions of animal shelter workers on the problems facing their industry. A sampling frame was constructed, consisting of every identified shelter in the UK, and a postal questionnaire sent to each. This included two open questions, soliciting respondents’ views on their biggest problems, and inviting further comments. A total of 661 respondents replied to at least one question. Thematic analysis on the free text content was carried out, and basic and global themes identified. Respondents’ main concerns centered on a mismatch between the continuous demand for their services and their limited resources, which has worsened during the recent financial crisis. Respondents perceived a need for increased public awareness of the commitment involved in keeping a pet, and of controlling breeding by neutering. Points of intervention, such as education programs, were suggested. Coordinating efforts with others, including local authorities, landlords, and housing associations, and a potential role for veterinary professionals working in shelter medicine were all explored by respondents. Rehoming organizations play an important role in the management of pet overpopulation, and the views and beliefs of their workers form an important contribution to the dialogue surrounding this issue. Consideration of these perspectives may suggest alternative routes to address underlying causes and management of pet overpopulation.